RELATIONSHIP BETWEEN FIBRE FLAX YIELD AND DIFFERENT FORMS OF NITROGEN IN THE SOIL (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2005)
Research on fibre flax yield response to the amount of different nitrogen forms in the soil was carried out at the Upytė Research Station of the Lithuanian Institute of Agriculture (LIA). Humus content (as a source of nitrogen) (%), total nitrogen (%), ammonium nitrogen (NH4+) (mg kg-1), nitrate nitrogen (NO3-) (mg kg-1), total mineral nitrogen (Nmin) (mg kg-1) were measured in the soil samples collected from the plough layer, and the correlation between the mentioned - above soil variables and fibre flax yield was calculated. In most cases the relationships were weak but significant. Seed, stem, and long fibre yields responded to the soil nitrogen differently. The strongest correlation was established between flax yield and humus content.